The Role of Tungku Tigo Sajarangan in Educating Adolescent Morality Through the Indigenous Values of Sumbang Duo Baleh - Hasan Basri; Mahyudin Ritonga; Mursal Mursal (AL-ISHLAH: Jurnal Pendidikan, 2022)
The flow of globalization and cultural acculturation on the one hand has an impact on the character of the generation of a nation, therefore local wisdom, participation of community leaders in creating a generation that is able to maintain a good local culture is highly expected. In line with that, this study aims to discuss the shape of the impact of Sumbang on Adolescent Girls, Tungku Tigo Sajarangan's Efforts in Educating Teens Through the Sumbang Duo Baleh Donation Custom, and how effective Tungku Tigo Sajarangan's efforts in Educating Teenagers Morals are through the Duo Baleh Donation Custom. The method used is a qualitative research method, which is also known as Naturalistic research. The primary data sources are ninik mamak, out-of-pocket clever, pious ulama and youth in Nagari Sungai Buluah. While the data collection technique uses observation, interviews and FGD with analytical techniques using interactive qualitative model analysis techniques (Interactive Model of Analysis). The results of the study indicate that the form of the impact of discord on adolescent girls is the fall of their identity as Minangkabau women, Mudarnyo Raso Jo Pareso, the erosion of Minang customary values. The efforts of Tungku Tigo Sajarangan in educating youth morals are carried out in various forms, such as giving warnings and traditional sanctions, conducting socialization in various places and activities, establishing cooperation between institutions, forming youth Wirid activities, holding traditional activities.